Faktor-Faktor yang Berhubungan dengan Kejadian Kehamilan Pada Akseptor KB - Siti Juhariah (Akademi Kebidanan La Tansa Mashiro, 2017)
The purpose of this study is the knowing factors - factors associated with the incidence of pregnancy in the family planning acceptors at the Maternity Hospital Anugerah Bogor City Year 2013. Type of research used is quantitative by using the Case Control study approach. The population in this study were all KB participants who visited RB Anugerah in 2012 - 2013. The number of samples between case and control is 1: 2 (35: 70). Thus, the total sample in this study was 105 KB participants. Univariate research results obtained from 105 respondents in the Maternity Hospital Anugerah Bogor in 2013 family planning acceptors who get pregnant as much as 43 (41.0%). The result of statistical test showed that there was no significant relationship between age, cost, type of contraception and husband support with pregnancy occurrence on KB acceptor. There is a significant correlation between knowledge, education level, discipline of re-control, and compliance with the incidence of pregnancy in the FP acceptor.Keywords: pregnancy in family planning acceptors, age, knowledge, education level, discipline of re-control, compliance, cost, type of contraception, husband support.